2018
DOI: 10.1136/heartjnl-2017-312819
|View full text |Cite
|
Sign up to set email alerts
|

Nut consumption and incidence of seven cardiovascular diseases

Abstract: BackgroundNut consumption has been found to be inversely associated with cardiovascular disease mortality, but the association between nut consumption and incidence of specific cardiovascular diseases is unclear. We examined the association between nut consumption and incidence of seven cardiovascular diseases.MethodsThis prospective study included 61 364 Swedish adults who had completed a Food Frequency Questionnaire and were followed up for 17 years through linkage with the Swedish National Patient and Death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 31 publications
0
33
1
Order By: Relevance
“…The mDASH and mMED diets were inversely associated with dietary fat intake in this study but none of the dietary patterns or any of the examined food groups were associated with incidence of AVS. In previous studies assessing the risk factors for AVS in this study population we observed no association with nut consumption specifically [44], but found an inverse association with light alcohol consumption [45]. To the best of our knowledge, no other epidemiologic study has assessed the association of any dietary pattern or specific foods or food groups with risk of AVS.…”
Section: Discussioncontrasting
confidence: 69%
“…The mDASH and mMED diets were inversely associated with dietary fat intake in this study but none of the dietary patterns or any of the examined food groups were associated with incidence of AVS. In previous studies assessing the risk factors for AVS in this study population we observed no association with nut consumption specifically [44], but found an inverse association with light alcohol consumption [45]. To the best of our knowledge, no other epidemiologic study has assessed the association of any dietary pattern or specific foods or food groups with risk of AVS.…”
Section: Discussioncontrasting
confidence: 69%
“…For walnuts specifically, a previous systematic review found improvements in total and LDL-cholesterol levels with consumption (55) . A further prospective study has highlighted the specific areas of heart disease in which nut consumption may be having its impact (56) . On the other hand, although fatty acids have been implicated in insulin sensitivity (34) , glycaemic control is more immediately influenced by carbohydrate in the diet, so any effect of nuts is likely to be seen as part of a preventive dietary pattern, as outlined below.…”
Section: Discussionmentioning
confidence: 99%
“…Becerra-Tomas et al, 2019 [8] recently showed that nut consumption lowered CHD mortality (396,041 subjects and 7877 CHD deaths) by 24% (RR = 0.76; 95% CI 0.67, 0.86; I 2 = 46%; p heterogeneity = 0.04) in a meta-analysis of 12 prospective studies (8 publications [12][13][14][15]19,[24][25][26]) comparing high with low nut consumption categories. The meta-analysis of Chen et al, 2017 [23] included 13 studies (10 publications) [13][14][15][16][17][18][19][26][27][28].…”
Section: Coronary Heart Disease Mortalitymentioning
confidence: 99%
“…When the meta-analysis by Becerra-Tomas et al, 2019 [8] was added [8,21,[30][31][32][33][34][35], a 17-34% reduction in CHD (or CAD) incidence was seen. Becerra-Tomas et al, 2019 [8] showed that nut consumption lowered incidence of CHD (275,812 subjects and 12,654 cases) by 18% (RR = 0.82; CI 95% 0.69, 0.96; I 2 = 74%; p heterogeneity < 0.01) in a meta-analysis of 7 prospective studies (5 publications [12,24,25,36,37]) comparing high with low categories of nut consumption.…”
Section: Coronary Heart Disease Incidencementioning
confidence: 99%